Effect of Financing Costs and Constraints on Real Investments: The Case of Inventories - Wu, Qi; Muthuraman, Kumar; Seshadri, Sridhar (Production and Operations Management, 2019)
This paper studies the effects of bank credit availability, trade credit and the capital cost on inventory decisions. There are two competing theories on the effect of bank credit lines on investments. While one (Lins et al. 2010) suggests that the primary role played by undrawn credit is to finance new opportunities, the other (Acharya et al. 2014) suggests that undrawn credit serves primarily as a bank monitored liquidity insurance. We attempt to resolve these two conflict views in the context of inventory investments. Using empirical data, we show that the primary role of undrawn credit depends on the individual firm’s financial status. When a firm is financially constrained, its inventory decisions are linked to the additional bank credit available to the firm—echoing the insurance nature of bank credits. On the other hand, when a firm is financially healthy, two other inventory financing factors play more significant roles than undrawn credits. For financially healthy firms, inventory investments are significantly negatively related to the financial cost of inventory and positively related to the credit offered by suppliers. Additionally, we study the financial crisis of 2007–2008 as a systematic shock in the credit market to identify the effects of a firm’s financial credits. We show that during the financial crisis, the inventory turnover and working capital levels of US retailers were related to the availability of bank credit. However, immediately after the crisis, the evidence demonstrates the positive relationship between firms’ inventory level and the trade credit they are offered.